Pertumbuhan rumput laut Kappaphycus alvarezii (Doty) yang direndam dalam ekstrak daun ketapang Terminalia catappa L. dengan frekuensi berbeda - Kurniawan, Putra M.; Kreckhoff, Reni L.; Ngangi, Edwin L. A.; Wagey, Billy T. (e-Journal BUDIDAYA PERAIRAN, 2020)
This study aimed to evaluate the benefits of Terminalia catappa L. leaf extract on the growth of Kappaphycus alvarezii seaweed. Treatment A (control /without soaking into ketapang leaf extract), treatment B (soaking into ketapang leaf extract at the beginning of maintenance), C (soaking ketapang leaf extract every 1 week) and D (soaking into ketapang leaf extract every 2 weeks). Differences in growth of K. alvarezii seaweed for 42 days were not significantly affected by differences in the frequency of immersion of ketapang leaf extract. Absolute growth of Fcount (3.9521977 tn) <Ftable value of 5% (4.06), relative growth of Fcount (2.957545 tn) <Ftable value of 5% (4.06) and daily growth rate of Fcount (3.237068tn) <Ftable value of 5% (4.06). Even so the results of absolute growth measurements, relative growth and the best daily growth rate on soaking ketapang leaf extract every two weeks, followed by soaking ketapang leaf extract at the beginning of cultivation, soaking ketapang leaf extract every one week and without soaking into leaf extract.